Subtractive modification of bacterial consortium using antisense peptide nucleic acids - Hizume, Tatsuya; Sato, Yu; Iwaki, Hiroaki; Honda, Kohsuke; Okano, Kenji (Frontiers in Microbiology, 2024)
Microbiome engineering is an emerging research field that aims to design an artificial microbiome and modulate its function. In particular, subtractive modification of the microbiome allows us to create an artificial microbiome without the microorganism of interest and to evaluate its functions and interactions with other constituent bacteria. However, few techniques that can specifically remove only a single species from a large number of microorganisms and can be applied universally to a variety of microorganisms have been developed. Antisense peptide nucleic acid (PNA) is a potent designable antimicrobial agent that can be delivered into microbial cells by conjugating with a cell-penetrating peptide (CPP). Here, we tested the efficacy of the conjugate of CPP and PNA (CPP-PNA) as microbiome modifiers. The addition of CPP-PNA specifically inhibited the growth of Escherichia coli and Pseudomonas putida in an artificial bacterial consortium comprising E. coli, P. putida, Pseudomonas fluorescens, and Lactiplantibacillus plantarum. Moreover, the growth inhibition of P. putida promoted the growth of P. fluorescens and inhibited the growth of L. plantarum. These results indicate that CPP-PNA can be used not only for precise microbiome engineering but also for analyzing the growth relationships among constituent microorganisms in the microbiome.